Teleworking After the Pandemic: Revealing Work-Home Conflicts, Job Ambiguity, and Work Stress - Indah Mulia Sari; Arsyad, Fachry (Universitas Negeri Semarang, 2025)
The transformation of work systems due to the COVID-19 pandemic has accelerated the adoption of teleworking as a permanent model within organizations. This shift presents psychosocial challenges, particularly regarding work-home conflict and work ambiguity, which are often associated with increased work-related stress. This study aimed to examine the influence of work home conflict and work ambiguity on job stress among employees engaged in post-pandemic teleworking in Indonesia. A quantitative regression design was employed, using data collected through an online questionnaire distributed to 139 purposively selected respondents. Simple linear regression was applied to assess the effect of the two independent variables on job stress. The findings revealed that neither work-home conflict nor work ambiguity had a statistically significant effect on job stress (p > 0.05), although the regression model showed an R² value of 41.5%. The conclusion of this study is that work-home conflict and work ambiguity do not show a significant relationship with work stress, indicating a possible change in the dominance of other stressor factors in the post-pandemic work environment. Practical implications highlight the need for organizations to shift their focus toward managing emerging stressors, such as digital fatigue, technological support, and flexible work boundaries.